Development and environmental applications of activated carbon cloths - Cukierman, Ana Lea (2013)
Activated carbon cloths have received growing attention because they offer comparative advantages over the traditional powdered or granular forms of this well-known adsorbent, providing further potential uses for technological innovations in several fields. The present article provides an overview of research studies and advances concerned with the development of activated carbon cloths and their use as adsorbent in environmental applications, mostly reported in the last years. The influence of some fabrics and textile wastes used as precursors, and of main activation process variables on the development and physicochemical, mechanical and/or electrical properties of the resulting activated carbon cloths are first reviewed. Then, investigations dealing with the removal of water and air pollutants by adsorption onto activated carbon cloths, including advances toward optimizing their regeneration after organic vapors saturation, are presented.